PEMUTUSAN HUBUNGAN KERJA SEPIHAK TERHADAP TENAGA KERJA ASING SEBELUM BERAKHIRNYA PERJANJIAN KERJA WAKTU TERTENTU (STUDI KASUS PUTUSAN NO. 595 K/PDT.SUS/2010) - Tito Aditya Nurgraha (Program Magister Ilmu Hukum Universitas Pancasila, 2018)
The use of foreign workers (TKA) in the Indonesian labor market is only for certain positionsand time. It is clearly regulated in Law no. 13 of 2003 on Manpower (Law No. 13 of 2003)and its implementing regulations. In practice, certain time labor agreements betweenemployers and foreign workers are often made by not meeting the applicable requirements.The restrictions are made through licensing system, limitation of foreign worker use incertain positions, and limitation of foreign worker use only in certain time workingrelationship. Meanwhile, PKWT arrangements for foreign workers based on Law no. 13 of2003 can not be implemented in absolute terms in the event of a violation of PKWT offoreign workers. This is due to the inconsistency between the provisions in Law no. 13 of2003 which limits the employment relationship of foreign workers only in certain timeworking relationship, while in others Law no. 13 Year 2003 also allows the transfer ofPKWT by law into PKWTT, in case PKWT is not fulfilled by the employer